Integrated pitchfork analysis : basic to intermediate level - Dologa, Mircea (John Wiley, 2008)
Integrated Pitchfork Analysis: Basic to Intermediate Level is an introductory text to the branch of Technical Analysis which uses the Andrews' pitchfork trading technique. Designed for traders with no experience of Pitchfork Analysis this book demonstrates how to analyse the markets and trade using pitchfork analysis, assisting the novice trader in achieving a consistent performance. Written by experienced trader, Dr Mircea Dologa, founder of www.pitchforktrader.com, the book begins by introducing and discussing the basic theory of p.